Plaque removal efficacy of Colgate 360 toothbrush: A clinical study - Nageshwar Iyer; Shalu Chandna; Abhishek Dhindsa; Dhanashree Damle; Ashish Loomba (Wolters Kluwer Medknow Publications, 2016)
Aim: The aim of this clinical study was to confirm the plaque removal efficacy of the Colgate 360 Whole Mouth Clean Toothbrush. Study Design: This was a single-center, monadic, case-controlled study with the 7 days duration. Materials and Methods: A total of eighty participants (56 male and 24 female) aged between 18 and 45 years with a minimum of 20 permanent teeth (excluding the third molars) without any prosthetic crowns and an initial plaque score of minimum 1.5 as determined by Modified Quigley-Hein Plaque Index (1970) participated in the study. There were two dropouts during the study duration, one male and one female. The participants were instructed to brush for 1 min, after which plaque index was recorded again. They were then instructed to brush their teeth twice a day for 1 min with the assigned toothbrush (Colgate 360 Whole Mouth Clean Toothbrush) and a commercially available fluoride toothpaste for the next 7 days. On the 7 th day, all the participants were recalled for follow-up and plaque examination. The plaque index scores (pre- and post-brushing) were recorded, tabulated, and analyzed statistically. Results: The mean plaque indices reduced after brushing both on day 1 and day 7. There was also a reduction in mean plaque indices from day 1 to day 7. All these reductions were statistically significant (P < 0.001). The reduction in plaque scores was independent of the gender of the participants however female participants showed lower scores as compared to male participants (P < 0.001). Conclusion: The present study demonstrated a significant reduction in plaque scores with the use of Colgate 360 Whole Mouth Clean Soft Toothbrush throughout the study period. Continued use resulted in a further significant reduction in plaque scores irrespective of the gender of participants.